Comparison of the Suggested loss Function with Generalized Loss Function for One Parameter Inverse Rayleigh Distribution - AL-Shareefi, Emad Farhood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiences in the life are considered important for many fields, such as industry, medical and others. In literature, researchers are focused on flexible lifetime distribution.In this paper, some Bayesian estimators for the unknown scale parameter  of Inverse Rayleigh Distribution have been obtained, of different two loss functions, represented by Suggested and Generalized loss function based on Non-Informative prior using Jeffery's and informative prior represented by Exponential distribution. The performance of   estimators is compared empirically with Maximum Likelihood estimator, Using Monte Carlo Simulation depending on the Mean Square Error (MSE). Generally, the preference of Bayesian method of Suggested loss function with Exponential informative prior are the best estimator compared to others.